Mobilizing the Social Power of Iconic and Performative Texts for Justice and Reform. Issue 2 (3rd March 2021) - Watts, James W.
Abstract : In the ten years of its existence, SCRIPT has succeeded in promoting and publishing an increasing variety of scholarship on iconic and performative texts. Culturally specific studies have provided the basis for comparative theorizing about the phenomena. This body of scholarship has put us in a better position to analyze current events involving iconic books and performative texts. It can also enable us to make creative suggestions for strengthening movements for justice and social reform by ritualizing iconic and performative texts. Here, I provide three examples of how to employ SCRIPT research to strengthen contemporary movements for social and environmental justice: a short-term episodic intervention, a medium-term structural rectification, and a long-term cultural innovation.